Plant toxicology - Elstner, Erich; Hock, Bertold (Marcel Dekker, 2005)
In order to keep track of all the compounds and pathogens affecting plant metabolism and development, you would need to spend all your waking hours combing periodicals and the Internet in dozens of languages, as new toxins via pollutants and migratory or mutant pathogens are being discovered every day. Plant Toxicology, Fourth Edition starts with a basic overview of the plant as a complex living organism. The first chapters introduce plant structure and organization. Starting with the cell as the smallest elementary unit, the emphasis is on plant-specific features with respect to their susceptibility to environmental contaminants. Hock and Elstner, who between them have published over 500 original papers on plants and plant disease, called upon experts from across the world to contribute to this essential text. The book analyzes processes central to plant metabolism, including uptake, distribution, and secretion of toxic material, and focuses on the recognition and prevention of damage associated with environmental pollutants. It studies diseases caused by viruses, subviral organisms, phytoplasmas, fungal and bacterial pathogens. Learn about Pathology in Plants as an Integral Interconnected Facet of their Environment The text is designed to enable you to classify and target specific forms of plant damage. Equally important, it never loses sight of the princple that plants are not isolated organisms, but rather exist as participants in complex environments, which must be taken into account when studying the delivery and impact of toxins. Supplying more than 1500 current references, Plant Toxicology, Fourth Edition is required reading for all plant, crop, soil, and environmental scientists; botanists; agronomists; agriculturists; horticulturists; biochemists; foresters; plant growers; and upper level undergraduate and graduate students in these disciplines.